Avaliação agronômica, físico-química e sensorial de híbridos de pimenta (Capsicum chinense Jacquin) - Martinez, Marcela (Universidade Federal de São Carlos, 2020)
The consumption of Capsicum peppers has been growing, encouraging cultivation and increasing the demand for new cultivars with better agronomic and nutritional qualities. The objective was to evaluate the agronomic, physical-chemical and sensory characteristics of five hybrids and a commercial open pollination cultivar (BRS Moema) of C. chinense pepper. The experiment was carried out in a protected environment in a completely block experimental design, with six replications and six treatments. The data were submitted to analysis of variance with subsequent grouping by the Scott & Knott test at 5%. The F1 23 hybrid was one of the most productive, with the highest value of total fresh fruit weight, average fruit weight, productivity, fruit diameter, pulp thickness and number of locules. For the physicalchemical analyzes, the hybrids F1 10, F1 12 and BRS Moema, obtained higher levelsof lipids, carbohydrates, phenolic and carotenoid compounds, total soluble solids and fibers. The F1 12 hybrid had a higher capsaicin content (12.73 mg g-1), while in F1 10 and F1 21 this was absent. For sensory analysis, the hybrids F1 12, F1 17 and F1 23, presented, respectively, greater sums for sweet aroma and pungency, size, color and sweet taste. The hybrids were superior to BRS Moema, for most of the evaluated characteristics, presenting high potential for the pepper agribusiness.
Agronomic, phisical-chemical and sensory evaluation of pepper hybrids (Capsicum chinense Jacquin)
Keywords: Capsaicina; Características antioxidantes; Melhoramento genético; Propriedades organolépticas; Pungência; Antioxidant characteristics; Capsaicin; Organoleptic properties; Plant breeding; Pungency; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA